Antipneumococcal activities of RP 59500 (quinupristin-dalfopristin), penicillin G, erythromycin, and sparfloxacin determined by MIC and rapid time-kill methodologies. - Pankuch, G A (1996)
Previous time-kill studies have shown that RP 59500 is rapidly bactericidal against pneumococci. To extend these findings, the activities of RP 59500, its two components RP 57669 RP 54476, penicillin G, erythromycin and sparfloxacin against 26 penicillin-susceptible, 25 penicillin-intermediate, and 25 penicillin-intermediate, and 25 penicillin-resistant pneumococci were determined by the agar dilution MIC and the time-kill testing methodologies within 10 min (ca. 0.2 h) and at 1 and 2 h. Respective agar dilution MICs at which 90% of isolates are inhibited for penicillin-susceptible, -intermediate, and -resistant strains were as follows: penicillin G, 0.03, 1, and 4 micrograms/ml;RP 59500, 1, 1, and 1 microgram/ml; RP 57669, 8, 32, and 16 micrograms/ml; RP 54476, > 128, > 128, and > 128 micrograms/ml; erythromycin, 0.06, 2, and > 128 micrograms/ml; and sparfloxacin, 1, 0.5, and 0.5 microgram/ml. RP 59500 was equally active (MIC at which 90% of isolates are inhibited, 1.0 microgram/ml) against erythromycin-susceptible and -resistant strains. Time-kill testing results showed that only RP 59500 at one to four times the MIC killed pneumococci at 0.2 h; RP 59500 was also the most active compound at 1 and 2 h. By comparison, penicillin and sparfloxacin at one, two, and four times the MICs reduced the original inoculum by > or = 1 log at 2 h for 46, 80, and 95% and for 50, 72, and 86% of strains, respectively. The killing activity of RP 59500 was the same against erythromycin-susceptible and -resistant strains. RP 57669, RP 54479, and erythromycin were either inactive or bacteriostatic at 2 h. Of all drugs tested, RP 59500 yielded the most rapid killing.